Development oF liveworksheets assisted by everycircuit to improve higher-order thinking skills of prospective elementary teacher - Siti Istiningsih; Nurul Kemala Dewi; Muhammad Erfan; Rahmat Hidayat; Mutmainnah Mutmainnah (JINoP (Jurnal Inovasi Pembelajaran), 2025)
Liveworksheets are an option for educators who teach subjects that involve practical activities, but learning that involves abstract concepts involving Higher-Order Thinking Skills (HOTS), such as electricity, requires another platform, such as Liveworksheets. The research aims were to develop digital learning media in the form of Liveworksheets assisted by the Android EveryCircuit application to improve Higher-Order Thinking Skills (HOTS) for prospective elementary school teacher students. This research and development use a 4D model consisting of define, design, develop, and disseminate. Data analysis was performed using quantitative descriptive methods. The results found that the Liveworksheet assisted by the Android EveryCircuit application was categorized as valid, with an average V-Aiken of 1.20. Liveworksheets were categorised as practical with a total average of 3.44 or 86%, statistically effective in improving students' higher-order thinking skills (HOTS) with the gain value of the experimental class in the medium category and the control class in the low category. Thus, the Liveworksheet Student Activity Sheet assisted by the Android EveryCircuit application developed is valid, practical, and effective in improving students' Higher-Order Thinking Skills (HOTS) in the subject matter of electricity in Elementary School Science Education courses.